Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.ijsu.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hepatoprotective effect from ischemia-reperfusion injury of remote ischemic preconditioning of the liver vs local ischemic preconditioning of the liver during human liver resections

Abstract: Strong evidence supports the hepatoprotective effect of RIPC and LIPC preconditioning from an ischemia-reperfusion injury of the liver. Better synthetic liver function preservation in these two groups supports this conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 38 publications
3
32
0
Order By: Relevance
“…22 Similarly, Rakić et al found reduction in transaminases and bilirubin in both RIPC (three 5-minute cycles on the arm) and IPC (15-minute of portal triad clamping then 10-minute reperfusion) in resection of liver colorectal metastasis. 23 However, this trial cannot conclude the absence of clinical hepatoprotective effect from RIPC, as there may be alternative reasons to explain the neutral results. First, a key consideration is the ubiquitous preference for propofol induction and inhalational maintenance in liver surgery among the anesthesiologists in our center.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…22 Similarly, Rakić et al found reduction in transaminases and bilirubin in both RIPC (three 5-minute cycles on the arm) and IPC (15-minute of portal triad clamping then 10-minute reperfusion) in resection of liver colorectal metastasis. 23 However, this trial cannot conclude the absence of clinical hepatoprotective effect from RIPC, as there may be alternative reasons to explain the neutral results. First, a key consideration is the ubiquitous preference for propofol induction and inhalational maintenance in liver surgery among the anesthesiologists in our center.…”
Section: Discussionmentioning
confidence: 82%
“…19 However, clinical trials in this area are fairly recent and there has been mixed clinical data from a small number of trials guiding the use of RIPC in liver surgery. [22][23][24] In this randomized controlled trial, we aimed to evaluate whether remote ischemic preconditioning (RIPC), could reduce acute liver injury following partial hepatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, preconditioning was performed with a tourniquet on the right upper limb, with 3 cycles of 5 minutes of ischemia followed by 5 minutes of reperfusion. The work suggests that the hepatoprotective effect is due to the reduction of cytokine release and activation of neutrophils, which decrease endothelial injury, in addition to the increase in vasoactive molecules, such as nitric oxide (NO), and activation of heat shock proteins that inhibit Effect of remote ischemic preconditioning on hepatic function after co2 pneumoperitoneum Santos JEF; et al apoptosis 20 . Further investigations about the role of these molecules and mechanisms in animal models of remote ischemic preconditioning are needed.…”
Section: Discussionmentioning
confidence: 99%
“…RIPC has potential to reduce liver injury following PH [73]. In addition, other clinical trial where RIPC was induced by three cycles of 5 min of ischemia of right upper limb followed by 5 min of reperfusion showed hepatic cytoprotective effects assessed by cholinesterase and bilirubin levels during liver resection [74]. Authors suggest that a shorter protocol of RIPC is safe and of equal effect, although the mechanisms of this effect must be investigated in future studies [74].…”
Section: Ripc In Liver Resectionsmentioning
confidence: 99%